MAKNA TOPE'LE'LENG DI DESA TANAH TOA KECAMATAN KAJANG KABUPATEN BULUKUMBA (ANALISIS SEMIOTIKA CHARLES SANDERS PIERCE) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This research discusses the meaning of Tope Le'leng in Tanah Toa Village, Kajang District, Bulukumba Regency. The subject matter raised in this study is (1) how Tope Le'leng means to the people of Tanah Toa and (2) factors that affect Le'leng production. The objectives in this study are two: (1) To see the meaning of tope Le'leng for the people of Tanah Toa and (2) factors that affect the production of Tope Le'leng. The study used qualitative research with Charles Sanders Pierce's semiotic model analysis approach. A sign or representation according to Charles is something that represents something else in some way or capacity. Something else is called an interpretant of the first sign referring to an object. Then the use of marks is used to mean black sarongs. The results showed that (1) the meaning of Tope Le'leng for the people of Tanah Toa is very important. Because Tope Le'leng is used by people who want to do a traditional event or ritual, such as wanting to enter Ammatoa and want to do weddings and death ceremonies. Tope Le'leng is also a characteristic of the Kajang Community because Tope Le'leng is different from other ordinary sarongs made by the people of Tanah Toa itself by weaving, and materials or tools made by the community itself. According to the people of Tanah Toa Tope Le'leng must be preserved and should not be overcome and most importantly Tope Le'leng is the source of livelihood of the Kajang people.